Therapeutic strategies against antibiotic resistance - Mitea, Gabriela; Schröder , Verginica; Iancu, Irina Mihaela; Iancu, Valeriu; Blebea, Nicoleta Mirela (Technium BioChemMed, 2023)
Antibiotics are the most important class of drugs and are one of the most influential medical inventions of the 20th century. Antibiotics have undoubtedly been a benefit to human society in the fight against bacteria, saving millions of lives. However, the number of infections caused by multidrug-resistant bacteria (MDR) is rising. Although antibiotics have enabled the development of several of medical practice, including the effective outcomes of several surgical and immunosuppressive therapies that rely on antibiotic prophylaxis and the potential to manage infectious complications, antimicrobial resistance poses significant challenge for all healthcare systems worldwide. As all organisms develop genetic mutations to prevent lethal selection, antimicrobial resistance is an inevitable evolutionary outcome. Bacteria will tend to develop and use resistance strategies as long as antibiotics are used against them. This review was based on the latest international information about therapeutic strategies against antibiotic resistance (by electronic search using Pubmed, SciFinder, Scirus, GoogleScholar and Web of Science).